FGFR3 mutation increases bladder tumourigenesis by suppressing acute inflammation. Issue 3 (19th September 2018) - Foth, Mona; Ismail, Nur Faezah Binti; Kung, Jeng Sum Charmaine; Tomlinson, Darren; Knowles, Margaret A; Eriksson, Pontus; Sjödahl, Gottfrid; Salmond, Jonathan M; Sansom, Owen J; Iwata, Tomoko
Abstract: Recent studies of muscle‐invasive bladder cancer show that FGFR3 mutations are generally found in a luminal papillary tumour subtype that is characterised by better survival than other molecular subtypes. To better understand the role of FGFR3 in invasive bladder cancer, we examined the process of tumour development induced by the tobacco carcinogen OH‐BBN in genetically engineered models that express mutationally activated FGFR3 S249C or FGFR3 K644E in the urothelium. Both occurrence and progression of OH‐BBN‐driven tumours were increased in the presence of an S249C mutation compared to wild‐type control mice. Interestingly, at an early tumour initiation stage, the acute inflammatory response in OH‐BBN‐treated bladders was suppressed in the presence of an S249C mutation. However, at later stages of tumour progression, increased inflammation was observed in S249C tumours, long after the carcinogen administration had ceased. Early‐phase neutrophil depletion using an anti‐Ly6G monoclonal antibody resulted in an increased neutrophil‐to‐lymphocyte ratio at later stages of pathogenesis, indicative of enhanced tumour pathogenesis, which supports the hypothesis that suppression of acute inflammation could play a causative role. Statistical analyses of correlation showed that while initial bladder phenotypes in morphology and inflammation were FGFR3‐dependent, increased levels of inflammation were associated with tumour progression at the later stage. This study provides a novel insight into the tumour‐promoting effect of FGFR3 mutations via regulation of inflammation at the pre‐tumour stage in the bladder. Copyright © 2018 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.